Trading Futures : A Theological Critique of Financialized Capitalism - Maia, Filipe, 1985- (Book collections on Project MUSE., 2022)
"Trading Futures offers a theological reflection about hope and the future in the context of financialized capitalism. Filipe Maia argues that capitalism has established an oppressive mode of imagining the future, where financialization becomes a process of privatizing hope, constraining our sense of what's possible. The hegemony of finance over our global economy has allowed it to construct the future in its image-predictable and manageable-colonizing the future for the sake of profit. The futures of finance promise wealth and prosperity but deliver, for most, economic inequality and the socialization of debt. Drawing on liberation theology, Marxist literature, and critical theory, the author proposes an eschatology of liberation as an alternative, subversive mode of imagining the future, a critical reflection on hope. Maia maintains that Christian eschatology offers a powerful tool for approaching and deconstructing questions of power, time, and equality. In addition, that eschatology provides the imagination and language to summon different realities and options using imagery, poetics, and prophecy. The mode of future-talk that the author weaves from his liberationist sources invokes different, unpredictable realities and options: critical pathways of resistance and potential escape routes from the injustice of financialized capitalism."--